KEPEMIMPINAN INOVATIF KEPALA MADRASAH DALAM MENGINISIASI PROGRAM VOKASI KONTEKSTUAL STUDI KASUS PROGRAM BARBERSHOP DI MAN 1 KABUPATEN GORONTALO - Bayu Saputra Dullah; Novianty Djafri; Pupung Puspa Ardini; Mohamad Zubaidi (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to analyze the innovative leadership practices of madrasah principals in initiating a contextual vocational education program through the Barbershop program at MAN 1, Gorontalo Regency. Using a qualitative approach with a case study design, data were obtained through semi-structured interviews, observations, and document analysis, then analyzed using thematic analysis. The results show that the madrasah principal's leadership is characterized by an adaptive, collaborative, and values-based vision, capable of responding to students' real needs and creating vocational learning that is relevant to the local social and economic context. The Barbershop program is a form of educational innovation that integrates technical skills, social responsibility, and Islamic values ​​such as trustworthiness and sincere work. The novelty of this study lies in the introduction of the concept of contextual vocational leadership, namely a leadership model that combines contextual sensitivity, collaboration, and moral values ​​in the management of vocational education in madrasahs. Practically, the results of this study provide guidance for Islamic education leaders and policymakers in designing vocational programs based on the local context and student character.